The Impact of Work-Life Balance on Academic Performance: A Study of Organizationally Active Students at STIE Sutaatmadja Subang - Yusnia Yusnia; Winda Nurfitri (STIESA Press, 2025)
University students often face dual demands from academic responsibilities and active participation in campus organizations. This dual role requires students to balance their time, psychological involvement, and satisfaction between academic and non-academic activities. This research aims to examine the influence of work-life balance, which includes time balance, involvement balance, and satisfaction balance, on the academic performance of students who are actively involved in campus organizations at STIE Sutaatmadja Subang. The research used a quantitative approach with purposive sampling involving 51 students who actively participate in organizations such as HIMA, BEM, DPM, and UKM. Data were collected through questionnaires based on the work-life balance dimensions developed by Greenhaus and Allen (2011) and analyzed using multiple linear regression with SPSS version 25. The results show that satisfaction balance has a significant positive effect on academic performance, while time balance and involvement balance do not have a significant effect. However, work-life balance as a whole simultaneously has a significant influence on academic performance. These findings indicate that student satisfaction in performing dual roles is a key factor in supporting academic success. Therefore, universities and student organizations need to create a conducive environment that allows students to maintain satisfaction and balance between their academic and organizational roles.